The Well-Being of the Elderly: Memory and Aging - Maldonado Briegas, Juan José; Sánchez Iglesias, Ana Isabel; Ballester, Sergio González; Vicente Castro, Florencio (Frontiers in Psychology, 2020)
The world population increases every day as a consequence of the increase in life expectancy and longevity of humans. There are several factors analyzed in the different studies that have been developed on this topic. The research carried out in this field distinguishes biological, cultural, and cognitive factors; some of them describing similar results, while many others showed antagonistic results. Our study was oriented to the accomplishment of a bibliographical revision with the objective to verify the scientific production on "memory, cognitive development, and aging linked with longevity" — international/national studies were analyzed and identified. The method carried out was through a research in the databases: SciELO, UAM, PePSIC, LILACS, PubMed, PsycINFO, Dialnet, and Teseo; in a period of 10 years, considering the studies published between January 2008 and December 2017. From the results found at first, 16 articles were analyzed after the application of the exclusion criteria. Likewise, we analyzed the relationship of longevity with the level of studies in Spain from a group of people over 60 years of age counted in January 2017. The literature review determined that there are psycho-cultural aspects that have a decisive influence on the increase in longevity, such as the performance of activities with positive mental states, positive emotions and experiences, and the level of studies